ANALISIS SPASIAL KERAWANAN GEMPA BUMI BERBASIS SISTEM INFORMASI GEOGRAFI (SIG) DALAM UPAYA MITIGASI BENCANA - Alwin; Ali Sya’ban; Agung Adiputra (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2020)
The earthquake that occurred in the south of Tasikmalaya caused quite severe damage in several areas, one of which was the Pangalengan District in Bandung Regency. The purpose of this research is to identify the impact of damage, specifically buildings due to the earthquake and identify physical and social factors that cause vulnerability in Pangelang District. The research method is descriptive qualitative, secondary data from the literature related to the problem being examined, in the form of regulatory documents, the results of previous studies related to the research location, interpretation and analysis of geological maps, maps of the earth, maps of earthquakes and land use. The results showed that geologically the physical condition of the land in the Pangalengan sub-district was prone to the threat of an earthquake disaster. Based on the assessment of land capability, including unstable land with typology of earthquake-prone type C areas, there are more than 2 mutually damaging factors. Rock types with weak physical properties, close to fault zones, steep slope and high earthquake intensity. In addition to geologically vulnerable land conditions, social factors also contribute to the level of damage, namely the condition of houses that are not earthquake-friendly, settlement patterns are clustered, the level of population density and community knowledge about disasters is still lacking.